Enhancement of Field Emission Properties of Carbon Nanotubes by ECR-Plasma Treatment. (27th October 2014) - Ali, Javid; Kumar, Avshish; Husain, Samina; Parveen, Shama; Choithrani, Renu; Zulfequar, Mohammad; Harsh,; Husain, Mushahid
Abstract : We report a significant improvement in electron field emission property of carbon nanotubes film by using an electron cyclotron resonance plasma treatment. Our research results reveal that plasma treatment can modify the surface morphology and enhance the field emission characteristics of carbon nanotubes. Raman spectra indicate that plasma treated CNTs sample has lesser defects. Before plasma treatment, low current density of 6.5 mA/cm 2 at 3.0 V/ μ m and at a high turn-on fieldE to of 2.4 V/ μ m was observed. ECR plasma treated CNTs showed a high current density of 20.0 mA/cm 2 at 3.0 V/ μ m and at a lowE to of 1.6 V/ μ m. The calculated enhancement factors are 694 and 8721 for ECR-plasma untreated and treated carbon nanotubes, respectively. We found an increase in the enhancement factor and emission current after the ECR-plasma treatment. This may be attributed to creation of geometrical features through the removal of amorphous carbon and catalyst particles.